Broad consent for health care-embedded biobanking: Understanding and reasons to donate in a large patient sample - Richter, Gesine; Krawczak, Michael; Lieb, Wolfgang; Wolff, Lena; Schreiber, Stefan; Buyx, Alena (Genetics in Medicine, 2018)
PurposeTo facilitate ethically acceptable and practically successful health care-embedded biobanking, the attitudes and understanding of patients and their motivation to participate need to be explored.MethodsA questionnaire study was conducted among 760 outpatients of a northern German university hospital to assess their awareness of, and motivation for giving broad consent to health care-embedded biobanking, also addressing the issue of feedback on individual-level research findings.ResultsThe overall willingness to give broad consent was high (86.9%) in our study, even though the subjective and objective understanding of patients was found to be only modest. Most participants who consented did so for prosocial reasons (altruism, solidarity, reciprocity, gratitude), whereas self-interest or worries about disadvantages played only a marginal role. Better objective understanding was associated with both a greater demand for feedback on individual research findings and a higher willingness to consent. Intermittent modification of the information material provided by the hospital led to significantly improved objective understanding.ConclusionPatient willingness to give broad consent to health care-embedded biobanking is high, with prosocial reasons driving decision making more than factual knowledge and approval or disapproval of specific consent elements. Future efforts to improve the information material used in health care-embedded biobanking should therefore emphasize prosocial reasons to consent.
CRIS-Team Scopus Importer:2023-03-08